Decision-Making Model for Addressing Role Conflict for Psychology Trainees When Supporting Family and Community - Larez, Natalie A.; Sharkey, Jill D. (Frontiers in Psychology, 2021)
As the field of psychology continues to make efforts to diversify the field, training programs must adapt to include the needs of diverse students. Universities in the United States mirror middle-class norms and values, which implies that students are expected to separate from familial roles and focus on their personal growth. This conflicts with core values and intentions of students from collectivist cultures. Although psychology trainees are obligated to adhere to professional ethical standards, a growing number of psychology trainees from collectivistic cultures need support to manage role conflict within potentially ambiguous standards regarding how to care for family and community members. This need is further complicated when training programs consider the lack of equitable access to mental health care resources in communities where their psychology trainees come from. In this paper, we engage in ethical decision making to address two scenarios representing role conflict between training program expectations and collectivist community and familial obligations. Through this exercise we develop and propose a Decision-Making Model for Addressing Role Conflict for Psychology Trainees. This conceptual model details a novel framework to assist psychology trainees when addressing the mental health of family and community while also providing guidance to help graduate training programs proactively equip their students with the skills and ethical framework they need to balance role conflicts such as when family and community members desire and need mental health support.